Peran Lima Pilar STBM di Rumah Tangga dalam Menurunkan Angka Stunting di Wilayah Kerja Puskesmas Jayapura Utara - Irjayanti, Apriyana; Irmanto, Maxsi; Fatiah, Mona Safitri; Aronggear, Mutiara S. D; Bouway, Nelson F J; Nauw, Jeqllyn J P; Nasifal, Alwi (Universitas Muhammadiyah Surakarta, 2025)
The prevalence of stunting in children is influenced by the state of sanitation in households. North Jayapura public health center is one of the public health centers in Jayapura City with the highest proportion of stunted children in 2020, at 26.3%. The objective of this initiative is to disseminate knowledge regarding the five fundamental principles of Community-Based Total Sanitation (STBM) within the domestic setting. The activity was conducted over a three-month period, from July to September 2024, within the operational scope of North Jayapura public health, the target population comprised women of childbearing age (WUS) or pregnant women (Bumil) and mothers with infants or toddlers who attended the Integrated Service Post (Posyandu). The number of target groups in this activity was 50 individuals, selected using the accidental sampling technique. The implementation of this activity employed a lecture method supported by animated images, followed by discussion and question-and-answer activities. The results of this activity demonstrated a statistically significant increase in knowledge, with an average gain of 12.0 points on a knowledge assessment of the five pillars of STBM in households, comparing the pre- and post-education groups, one statement, namely the one concerning septic tanks, has yet to achieve a satisfactory score. This is due to the fact that it is one of the methods used to treat household liquid waste.